Bionic Prostheses: The Emerging Alternative to Vascularised Composite Allotransplantation of the Limb - Amin, Kavit R.; Fildes, James E. (Frontiers in Surgery, 2022)
Twenty years have surpassed since the first vascularised composite allotransplantation (VCA) of the upper limb. This is an opportunity to reflect on the position of VCA as the gold standard in limb reconstruction. The paucity of recipients, tentative clinical outcomes, and insufficient scientific progress question whether VCA will remain a viable treatment option for the growing numbers of amputees. Bionic technology is advancing at a rapid pace. The prospect of widely available, affordable, safely applied prostheses with long-standing functional benefit is appealing. Progress in the field stems from the contributions made by engineering, electronic, computing and material science research groups. This review will address the ongoing reservations surrounding VCA whilst acknowledging the future impact of bionic technology as a realistic alternative for limb reconstruction.